Oracle advanced PL/SQL developer professional guide : master advanced PL/SQL concepts along with plenty of example questions for 1Z0-146 examination - Gupta, Saurabh K. (Enterprise : professional expertise distilled., 2012)
Master advanced PL/SQL concepts along with plenty of example questions for 1Z0-146 examination.